Role of information and communication technologies in the development of listening skills of non-linguistic students at a technical university - Nina S. Shvaikina; Alexander A. Popel (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This paper focuses on a particular type of modern technologies, i.e. information and communication technology which has emerged as part of digital didactics. These technologies have brought about dramatic changes in all walks of life as well as in our expectations of what students should learn to survive in a new technological world. In their future work students will have to deal with large volumes of information obtained digitally, to use digital tools to work not only in Russian, but also in a foreign language (English). Consequently, it is necessary to teach them how to operate digital tools while teaching them the language. Among the most challenging speech activities, it is listening comprehension that challenges learning the most and requires longer time to develop at technical university due to insufficient number of hours given to the discipline called Foreign (English) Language in engineering faculties. Thus, the object of the research is the process of developing listening skills of nonlinguistic students in foreign (English) language classes. The subject of the research is interactive tasks based on web-services, aimed at developing their listening skills. The aim of the research is to create and test listening comprehension tasks on the platform of web services during lessons of foreign (English) language for students of non-language direction at technical university. To follow up listening skills and search for new audio texts the authors suggest using Randall's ESL Cyber Listening Lab resource and AI-based Andy application which simulates native speech. Based on a four-month (one semester) experiential study these resources have proven themselves effective.